Chromium (VI) Inhibition of Low pH Bioleaching of Limonitic Nickel-Cobalt Ore - Santos, Ana Laura; Dybowska, Agnieszka; Schofield, Paul F.; Herrington, Richard J.; Cibin, Giannantonio; Johnson, D. Barrie (Frontiers in Microbiology, 2022)
Limonitic layers of the regolith, which are often stockpiled as waste materials at laterite mines, commonly contain significant concentrations of valuable base metals, such as nickel, cobalt and manganese. There is currently considerable demand for these transition metals, and this is projected to continue to increase (alongside their commodity values) during the next few decades, due in the most part to their use in battery and renewable technologies. Limonite bioprocessing is an emerging technology that often uses acidophilic prokaryotes to catalyse the oxidation of zero-valent sulfur coupled to the reduction of Fe (III) and Mn (IV) minerals, resulting in the release of target metals. Chromium-bearing minerals, such as chromite, where the metal is present as Cr (III), are widespread in laterite deposits. However, there are also reports that the more oxidised and more biotoxic form of this metal (Cr (VI)) may be present in some limonites, formed by the oxidation of Cr (III) by manganese (IV) oxides. Bioleaching experiments carried out in laboratory-scale reactors using limonites from a laterite mine in New Caledonia found that solid densities of ~10% w/v resulted in complete inhibition of iron reduction by acidophiles, which is a critical reaction in the reductive dissolution process. Further investigations found this to be due to the release of Cr (VI) in the acidic liquors. X-ray absorption near edge structure (XANES) spectroscopy analysis of the limonites used found that between 3.1 and 8.0% of the total chromium in the three limonite samples used in experiments was present in the raw materials as Cr (VI). Microbial inhibition due to Cr (VI) could be eliminated either by adding limonite incrementally or by the addition of ferrous iron, which reduces Cr (VI) to less toxic Cr (III), resulting in rates of extraction of cobalt (the main target metal in the experiments) of >90%.